Analysis of the Role of Internal Auditors in Improving Financial Management Accountability Region: Literature Studies of the Last 5 Years - Risalatul Hidayah; Sri Wahyuni; Dewi Rismatul Jannah; Mohamad Djasuli (COMPETITIVE, 2025)
This study aims to analyze the role of internal auditors in improving accountability in regional financial management. Internal auditors play a crucial role in ensuring that financial management is conducted transparently, accountably, and in accordance with applicable regulations. This study uses a quantitative approach through a literature review of various previous studies and case studies of related documents. The results indicate that internal auditors function as supervisors, consultants, and advocates in improving financial management accountability. However, the effectiveness of this role is influenced by factors such as auditor independence, human resource qualifications, and support from regional leaders. This study concludes that the role of internal auditors needs to be strengthened to ensure more transparent and accountable regional financial governance.Â